Social Activity of A Personality - Lazauskas, Justinas (Problemos, 1969)
The article presents the analysis of some methodological problems arising in the study of social activity of a personality. Upon the analysis of some theses available in the literature on the question, the author concludes that social activity of a personality is its essential feature. As a process it has its own structure, determining its state, tendency and character. At the same time social activity of a personality appears in the role of a relationship in the activity exchange system, asserting freedom for individuality and thanks to this creating prerequisites for its self-expression. The essence of the social mechanism in question is necessity-interest-aim. Self-consciousness plays a major part in that: as an aim it appears in the role of a definite value orientation.